A rabbit anti-human CD38 antibody for eliminating daratumumab and isatuximab interference in immunohematology testing - Zhang, Liangzi; Zhang, Yinze; Qi, Jun; Su, Xiaomin; Zuo, Qinqin; Yan, Fang; Cui, Ying; Li, Na; Dong, Yanying; Xu, Hua (Frontiers in Immunology, 2026)
Anti-CD38 antibodies such as daratumumab (DARA) and isatuximab (ISA), used in multiple myeloma (MM) therapy, bind to CD38 on red blood cells (RBCs), leading to pan-agglutination in indirect antiglobulin tests (IATs) and interfering with pretransfusion testing. Given the frequent need for transfusions in MM patients with anemia, resolving this interference is clinically essential. While dithiothreitol (DTT) is commonly used, it compromises clinically important RBC antigens. To address this limitation, a novel approach was developed using a recombinant rabbit anti-human CD38 IgG monoclonal antibody, D2, to treat RBCs. Rabbits were immunized with hCD38-His. Antigen-specific B cells were isolated via flow cytometry and subsequently sequenced to obtain the antibody genes. After cloning and expression, a rabbit mAb named D2 was selected for its ability to bind the CD38 on human RBCs and block the binding of therapeutic anti-CD38 antibodies without affecting other RBC blood group antigens. Incubation of 1 μL of packed RBCs with 3 μL of 1 mg/mL D2 for 10 minutes at room temperature eliminated DARA- or ISA-induced pan-agglutination in the IAT while preserving the detection of clinically significant irregular antibodies. Its efficacy was confirmed using samples from 48 DARA- or ISA-treated patients. D2 is stable, easy to use, and suitable for routine application in transfusion laboratories to resolve anti-CD38-induced interference in pretransfusion testing.